2021
DOI: 10.3390/nu13041161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mediterranean Diet, Dairy, and Meat Products on Different Phenotypes of Dyslipidemia: A Preliminary Retrospective Analysis

Abstract: Background: Dyslipidemia is one of the major causes of atherosclerotic cardiovascular disease (ASCVD) and a Mediterranean Diet (MD) is recommended for its prevention. The objectives of this study were to evaluate adherence to an MD at baseline and follow-up, in a cohort of dyslipidemic patients, and to evaluate how different food intakes can influence lipid profile, especially how different sources of saturated fatty acids impact lipid phenotype. Methods: A retrospective analysis was conducted on 106 dyslipide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In total, 23 studies evaluated the level of MD adherence on WC with a significantly inverse pooled effect being found. HDL-c was assessed by 39 studies (N = 31,800 individuals) and the pooled effect showed increased levels with higher MD adherence, while TG were found significantly lower, in agreement with other studies included in the Special Issue [3,6,7].…”
supporting
confidence: 84%
See 3 more Smart Citations
“…In total, 23 studies evaluated the level of MD adherence on WC with a significantly inverse pooled effect being found. HDL-c was assessed by 39 studies (N = 31,800 individuals) and the pooled effect showed increased levels with higher MD adherence, while TG were found significantly lower, in agreement with other studies included in the Special Issue [3,6,7].…”
supporting
confidence: 84%
“…These results underline that in addition to the dietary transition seen the past decades in this region, the pandemic has further triggered unhealthy dietary choices that may further increase metabolic diseases, and the authors agree with Grabia and colleagues [ 2 ] and recommend dietary counseling to increase fruits, vegetables, and other foods close to the MD pattern. Moreover, the importance of dietary counseling on the lipid profile in healthy [ 6 , 7 ] and dyslipidemic individuals [ 3 ] was evident by intervention studies included in the present SI.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…27,29 In addition, a recent study observed that the consumption of dairy products was associated with higher TC, LDL-C, and HDL-C levels in patients with dyslipidemia. 30 Owing to the lack of data on dietary consumption in KNHANES, especially in adolescents aged 10-11 years, our study could not determine the possible association between the changes in lipid profiles and nutritional factors. However, a simultaneous increase in TC, HDL-C, and LDL-C levels in Korean adolescents suggests a possible role of changes in dietary fat or dairy consumption in this population; further studies are warranted in the future.…”
Section: Discussionmentioning
confidence: 88%